2021
DOI: 10.32732/jcec.2021.10.4.225
|View full text |Cite
|
Sign up to set email alerts
|

Pumice as Precursor in Geopolymer Paste and Mortar

Abstract: Natural rocks of magmatic origin are alternative precursors in alkali-activated materials and provide opportunities in the search for more environmentally friendly binders compared to portland cement. The pumice is one of these rocks and its amorphous structure and chemical composition make it one of the candidates as a precursor in producing geopolymer binder when finely ground. Since the majority of the pumice reserves are located in Turkey increases its potential utilization in this area, even more. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Pumice stone is used in the construction industry as a lightweight aggregate, and the powder is often used as a partial cement replacement due to its pozzolanic properties [36]. In geopolymer development, pumice stone is used in its powdery form (pumice powder-PP) as either a partial replacement of another precursor-based geopolymer or as the main precursor material due to its richness in Al and Si content [37,38]. Nematollahi et al [39] confirmed the feasibility of a one-part FA geopolymer activated with NaOH and Na 2 SiO 3 in the powder form and obtained a compressive strength of 29 N/mm 2 , which was comparable to the two-part formulation when NaOH and Na 2 SiO 3 alkaline solutions were employed as the activators.…”
Section: Introductionmentioning
confidence: 99%
“…Pumice stone is used in the construction industry as a lightweight aggregate, and the powder is often used as a partial cement replacement due to its pozzolanic properties [36]. In geopolymer development, pumice stone is used in its powdery form (pumice powder-PP) as either a partial replacement of another precursor-based geopolymer or as the main precursor material due to its richness in Al and Si content [37,38]. Nematollahi et al [39] confirmed the feasibility of a one-part FA geopolymer activated with NaOH and Na 2 SiO 3 in the powder form and obtained a compressive strength of 29 N/mm 2 , which was comparable to the two-part formulation when NaOH and Na 2 SiO 3 alkaline solutions were employed as the activators.…”
Section: Introductionmentioning
confidence: 99%
“…Raw materials or precursors, activator/activator solution, particle size, calcination temperature, or thermal treatment and processing are all important factors that can influence geopolymer properties [29][30][31][32]. Furthermore, the outcomes of the compressive testing of binder materials are critical because they are the primary parameters used to evaluate the quality of the test object.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete is the most widely utilized material in the construction industry throughout the world [1,2]. Cement, natural sand, coarse aggregate, and water are the major ingredients of concrete.…”
Section: Introductionmentioning
confidence: 99%